VALUATION OF BIOTECHNOLOGY COMPANIES: REAL OPTIONS APPROACH UNDER UNCERTAINTY - Ljumović, Isidora; Cvijanović, Janko; Lazić, Jelena (Economics of Agriculture, 2012)
Biotechnology is one of the most intensive industries in the past few decades. Essence of their operations leads to problem of determining the value of biotechnology companies, because in addition to their existing value, future product, market opportunities and intangible assets are difficult to value. Biotech companies dont have a standard format, and simple techniques, such as financial statements analysis or discounted cash flows cannot be applied. Due to the complexity of their work and high levels of risk, alternative method such as real options is applied. The concept of financial options can be extended to the valuation of investment opportunities in commercial companies, especially in biotech. This paper explains how real options provide various perspectives on the project (investment) value in relation to situations in which the project is: delayed, expanded, abandoned, business is contracted, operations are switched, products with multiple applications are grown, and optimal date for the product launch is determined.